Unidades de paisagens e saberes locais: estratégias para o planejamento ambiental no Arquipélago do Bailique na Amazônia Oriental - Sousa, Francele Benedito Baldez de (2023)
Taking as theoretical and methodological reference the Geoecology of Landscapes, this work aimed to identify and characterize the geoenvironmental units of the Bailique – AP archipelago, in view of an integrated diagnosis that could support planning strategies and environmental management based on the vulnerabilities, potentialities and limitations identified in the study area. In the construction and organization of the methodological process, we sought to privilege the dialogical interactions between the different spheres of society, evidencing local knowledge as indispensable and necessary knowledge in the elaboration of an efficient environmental planning and for participatory territorial management, because it is understood that only technical-scientific knowledge is not sufficient to the process of spatial organization. The dynamics of each stage of the work were thought and discussed together with community organizations, respecting the principles established by the Community Protocol of Bailique and approved in advance by local leaders. As for the research techniques, they were questionnaires, direct observation, social cartography, field activities and map construction. It is emphasized that the forms of use and disorderly occupation in the research area of this thesis have been gradually causing changes in landscapes, and compromising the environmental balance, as well as the quality of life of local populations. Therefore, the present thesis comprises a holistic analysis of the dynamics of the landscapes of the Bailique Archipelago, interdisciplinary and integrated with local knowledge, aiming at the characterization of socio-environmental problems, their limitations and potentialities, in an approach based on the science of Landscape Geoecology and the ecology of knowledge.